Phytosomal delivery enhances bioactivity of Hylocereus costaricensis phenolic extract - Direito, Rosa; Sousa, Inês; Antunes, Filipa; Barbalho, Sandra Maria; Simões, Sandra; Bronze, Maria Rosário; Reis, Catarina; Gaspar, Maria Manuela; Figueira, Maria Eduardo (Frontiers in Nutrition, 2025)
IntroductionConsuming foods rich in bioactive compounds can delay chronic non-communicable diseases. Dragon fruit, known for its bioactive compounds with typically low bioavailability—attributed to high polarity, poor permeability, and rapid firstpass metabolism—benefits from strategies like encapsulation to enhance efficacy.MethodsThis study developed and assessed phytosomes loaded with dragon fruit extract (Hylocereus costaricensis) and compared their biological activity in vitro and in vivo against the raw extract. Spectrophotometric analysis of the extract revealed 410.4 mg GAE/L of total phenolic compounds and 139.3 mg CE/L of flavonoids. HPLC-DAD-MS/MS identified key components such as citric acid, succinic acid, cyanidin-3-O-rutinoside, ferulic acid, betanin, and rutin. Phytosomes encapsulated 46 ± 2% of phenolics, with a mean diameter of 1,329 ± 121.0 nm, PDI 0.633 ± 0.039, and ζ-potential −16 ± 1 mV.ResultsAntioxidant capacities, assessed by the DPPH method, showed that the phytosomal formulation with 46% phenolic content was as effective as the raw extract. In vivo antihyperglycemic studies showed no significant effect from the raw extract (5 mg GAE/kg), but phytosomes (2.3 mg GAE/kg) matched the efficacy of metformin (300 mg/kg). An acute inflammation model using carrageenan-induced paw edema indicated that phytosomes (2.3 mg GAE/kg) had superior anti-inflammatory effects compared to the raw extract (5 mg GAE/kg).DiscussionIn summary, dragon fruit extract has antioxidant, antihyperglycemic, and anti-inflammatory properties. These findings support that phytosomal encapsulation significantly improves the bioavailability and efficacy of phenolic-rich crude extract, highlighting their potential in functional food development, nutraceutical applications, and as helpers to conventional therapeutic strategies.